Evaporation and carbonic anhydrase activity recorded in oxygen isotope signatures of net CO2 fluxes from a Mediterranean soil - Wingate, Lisa; SEIBT, ULLI; MASEYK, KADMIEL; OGÉE, JÉRÔME; Almeida, Pedro; YAKIR, D. A. N.; Pereira, João S.; MENCUCCINI, MAURIZIO (Global Change Biology, 2008)
The oxygen stable isotope composition (δ18O) of CO2 is a valuable tool for studying the gas exchange between terrestrial ecosystems and the atmosphere. In the soil, it records the isotopic signal of water pools subjected to precipitation and evaporation events. The δ18O of the surface soil net CO2 flux is dominated by the physical processes of diffusion of CO2 into and out of the soil and the chemical reactions during CO2–H2O equilibration. Catalytic reactions by the enzyme carbonic anhydrase, reducing CO2 hydration times, have been proposed recently to explain field observations of the δ18O signatures of net soil CO2 fluxes. How important these catalytic reactions are for accurately predicting large-scale biosphere fluxes and partitioning net ecosystem fluxes is currently uncertain because of the lack of field data. In this study, we determined the δ18O signatures of net soil CO2 fluxes from soil chamber measurements in a Mediterranean forest. Over the 3 days of measurements, the observed δ18O signatures of net soil CO2 fluxes became progressively enriched with a well-characterized diurnal cycle. Model simulations indicated that the δ18O signatures recorded the interplay of two effects: (1) progressive enrichment of water in the upper soil by evaporation, and (2) catalytic acceleration of the isotopic exchange between CO2 and soil water, amplifying the contributions of ‘atmospheric invasion’ to net signatures. We conclude that there is a need for better understanding of the role of enzymatic reactions, and hence soil biology, in determining the contributions of soil fluxes to oxygen isotope signals in atmospheric CO2.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: atmospheric invasion; carbonic anhydrase; Drought; Mediterranean forests; oxygen isotopes; Quercus suber; Soil CO2 efflux; soil evaporation; soil water δ18O composition

Evaporation and carbonic anhydrase activity recorded in oxygen isotope signatures of net CO2 fluxes from a Mediterranean soil (Global Change Biology, 2008)
The oxygen stable isotope composition (δ18O) of CO2 is a valuable tool for studying the gas exchange between terrestrial ecosystems and the atmosphere. In the soil, it records the isotopic signal of water pools subjected to precipitation and evaporation events. The δ18O of the surface soil net CO2 flux is dominated by the physical processes of diffusion of CO2 into and out of the soil and the chemical reactions during CO2–H2O equilibration. Catalytic reactions by the enzyme carbonic anhydrase, reducing CO2 hydration times, have been proposed recently to explain field observations of the δ18O signatures of net soil CO2 fluxes. How important these catalytic reactions are for accurately predicting large-scale biosphere fluxes and partitioning net ecosystem fluxes is currently uncertain because of the lack of field data. In this study, we determined the δ18O signatures of net soil CO2 fluxes from soil chamber measurements in a Mediterranean forest. Over the 3 days of measurements, the observed δ18O signatures of net soil CO2 fluxes became progressively enriched with a well-characterized diurnal cycle. Model simulations indicated that the δ18O signatures recorded the interplay of two effects: (1) progressive enrichment of water in the upper soil by evaporation, and (2) catalytic acceleration of the isotopic exchange between CO2 and soil water, amplifying the contributions of ‘atmospheric invasion’ to net signatures. We conclude that there is a need for better understanding of the role of enzymatic reactions, and hence soil biology, in determining the contributions of soil fluxes to oxygen isotope signals in atmospheric CO2.